Professional Practices of Human Resource Management in Hong Kong : Linking HRM to Organizational Success - Lai, K. T.; Tsui, Anna P. Y. (Book collections on Project MUSE., 2009)
This book distills over decades of professional experience of the contributors as HR professionals, consultants, legal experts/advisors and academics. It shares the full spectrum of professional HRM practices in relation to their strategic contributions to organizations. In a hands-on and lively fashion, it provides up-to-date HRM knowledge and skills with practical guidelines to various stakeholders of HRM so as to equip them with theoretical and practical knowledge that they would have good impacts on business results and add value.